Headache diagnosis in an urgency and emergency unit: Public Health Relevance and its relationship with cost - Oliveira, Ligia Barros; Guimarães, Jessica; Silva, Danilo Jorge da; Jurno, Mauro Eduardo (Headache Medicine, 2021)
Background Headache is a common symptom that affects a significant portion of the general population. It constitutes a challenge for diagnosis in urgency and emergency care services, due to headache’s clinical variability and diverse possible etiologies, besides the limited time and resources of these facilities. Because of this insufficiency and the potential severity associated with the condition, headaches generate considerable expenditures to health systems, related to both diagnostic discrimination and treatment. Objective Evaluating the diagnostic resources used on headache patients care, as well as its Public Health Relevanceand relation to cost in an Emergency and Urgency Care unit. Methods Cross-section study analyzing 450 medical records of patients with headache complaints in the time frame from January 1, 2019, and December 31, 2019. Patients were categorized according to the type of headache (primary and secondary), specialized evaluation, complementary exams used in the diagnosis, hospital observation time, and the final expenditure in each patient’s care. Results The total estimated expenditures related to headache care equaled US90,855.60 (average US201.90 per patient). 38.9% of cases corresponded to primary headaches and 31.1% to secondary headaches. 30% of cases could not be classified. The resources utilized for secondary headaches diagnosis differed significantly from those used in primary headache diagnosis. However, the final expenditures were similar to both groups. Conclusion The socio-economic impact caused by headaches is unquestionable. It is a highly frequent symptom and both its etiological distinction and adequate treatment require solid evaluation. Due to the resources spent in its evaluation and monitoring, headaches can be considered a public health problem. Therefore, this study suggests that resources should be allocated in the health education and professional training for the proper conduction of these patients, so that they may benefit from an optimized treatment of their condition without overwhelming the health system.